J2 Predictive testing for huntington's disease (HD) on those under 18 years: the UK experience 1994–2015. (13th September 2016) - Quarrell, Oliver; Cann, Rachael; Fryer, Alan; Jenkins, Sian; O'Driscoll, Mary; Lahiri, Nayana; Compton, Celia; Musgrave, Hannah; Miedzybrodzka, Zosia; Clarke, Angus; Macleod, Rhona
Abstract : Background: A consistent feature of predictive testing guidelines for HD has been recommendations not to undertake predictive tests on those <18 years. However, it is known that exceptions are made. Since 1989 a UK HD Prediction Consortium (UKHPC) has been established to collect data annually on the number of predictive tests which have been undertaken from 23 genetic centres in the UK. Aims: To identify the extent of predictive testing on minors between 1994–2015 and, where possible, identify the reasons for undertaking the predictive test on a minor. Methods: The UKHPC database was inspected for the number of predictive tests on those <18 years. Each genetic centre was contacted asking for more details on the reasons for testing. Results: There were 9616 tests on the database with 9466 having an age of testing recorded. 63 tests were reported on those <18 years but subsequently 2 entries were and 1 was symptomatic. The extent of testing of those <18 years in the UK is 60/9466 = 0.63%. The majority of the tests were done on those aged 17 years and 16 years and these account for 57% and 23% of the tests on minors respectively. Data on the reasons for testing were identified for 27 cases and included: close to the age of 18 years, pregnancy, currently in care and more support available <18 years, person never having the capacity to consent and some miscellaneous reasons to be described individually. Conclusion: This study documents the extent of HD testing of minors in the UK and suggests that, in general, the recommendations are working. Exceptions are being made and we provide some empirical evidence as to reasons why clinicians have chosen to depart from the recommendation not to test minors. We do not advise changing the recommendation but suggest that testing of minors continues to be monitored.